Design, synthesis, multipotent antioxidant activity of new heterocycles and some reactions of acid hydrazide based on butylated hydroxytoluene (BHT) moiety / Wageeh A. Yehye - Yehye, Wageeh A. (2012)
This work involves searching and designing of MPAO. To obtain MPAO, one can screen drug collections and/or antioxidant-product libraries, or couple an antioxidant group with other antioxidant pharmacophores. Therefore, de novo antioxidant design strategy provides important clues as to how the design concept for MPAO can be improved. Accordingly, novel 1-acylthiosemicarbazides (4.4-4.6), 1,3,4-thiadiazoles (4.7-4-9), 1,2,4-triazoles (4.10-4.12), and 4-amino-1,2,4-triazole-5-thione derivatives (4.14-4.20) bearing the well-known free radical scavenger (BHT) were designed and synthesized. To verify the antioxidant activity of the designed MPAO, two different established in vitro antioxidant assays, DPPH and lipid peroxidation were used. Synthesised BHT derivatives (4.4-4.12) were examined for their capacity to scavenge stable free radical (DPPH˙) and their ability to inhibit lipid peroxidation using well-known standard antioxidant, BHT and α-TOH as well as the compound 4.1. Compounds 4.4-4.12 showed inhibition of DPPH stable free radicals at 10-4 M more than the well-known standard antioxidant BHT and starter compound 4.1. Compound 4.12 is the most potent in the in vitro lipid peroxidation and exhibited promising in vitro inhibition of Fe2+-induced lipid peroxidation of essential oils, using egg yolk as a lipid-rich medium (86.4%, IC50 2.85 ± 1.09 μM/ml) while α-TOH (84.6%, IC50 5.6 ±1.09 μM/ml). X-ray structure of 4.11 emphasized the contribution of stereoelectronic substituent effects (o- methoxy group) on the inhibition results obtained in both DPPH and lipid peroxidation assays, resulted in 27% and 76% inhibition while in the absence of stereoelectronic effects, 4.12 (p-methoxy group) resulted in 52% and 86% inhibition, respectively. The work then continued with the investigation of some reactions of hydrazide (4.3) under different conditions of experiment and reagents. The results promoted novel synthetic approaches for the preparation of diarylsemicarbazones and symmetrical azines to be new indirect hydrazination procedure, which could allow future researchers to carry out studies to prepare diarylsemicarbazone bearing active carbonyl groups and other functional groups sensitive to hydrazine hydrate.